2016
DOI: 10.1016/j.psyneuen.2016.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Perceived neighborhood problems are associated with shorter telomere length in African American women

Abstract: Objectives African Americans (AA) experience higher levels of stress related to living in racially segregated and poor neighborhoods. However, little is known about the associations between perceived neighborhood environments and cellular aging among adult AA. This study examined whether perceived neighborhood environments were associated with telomere length (TL) in AA after adjustment for individual-level risk factors. Methods The analysis included 158 women and 75 men AA aged 30 to 55 years from the Moreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 53 publications
2
34
2
Order By: Relevance
“…Low SES is believed to increase stress levels, and differences in SES are commonly cited as a possible explanation for differences in TL between African Americans and European Americans (eg, Gebreab et al, ; Geronimus et al, ; Needham et al, ; Theall et al, ). While many of these studies have found inverse associations between measures of SES and both TL and rate of telomere shortening in African Americans (eg, Needham et al, ; Schrock et al, ), others have failed to do so, while simultaneously reporting associations that link TL with discrimination (Chae et al, ; Lee et al, ; this study).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low SES is believed to increase stress levels, and differences in SES are commonly cited as a possible explanation for differences in TL between African Americans and European Americans (eg, Gebreab et al, ; Geronimus et al, ; Needham et al, ; Theall et al, ). While many of these studies have found inverse associations between measures of SES and both TL and rate of telomere shortening in African Americans (eg, Needham et al, ; Schrock et al, ), others have failed to do so, while simultaneously reporting associations that link TL with discrimination (Chae et al, ; Lee et al, ; this study).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to discrimination, chronic stress stemming from differences in SES is often investigated as a possible explanation for disparities in rates of telomere shortening between African Americans and European Americans (Gebreab et al, ; Geronimus et al, ; Needham et al, ; Theall, Brett, Shirtcliff, Dunn, & Drury, ). Financial strain, education years completed, and household income are some of the most commonly tested SES measures, and all have been associated with either shorter TL or increased telomere attrition in African American cohort studies (Needham et al, ; Schrock et al, ; Shiels et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Growing evidence suggests that accelerated biological aging at the cellular-and molecular-levels may help to explain the mechanisms linking adverse neighborhood environments to mortality (12)(13)(14)(15)(16)(17)(18)(19). Epigenetic mechanisms, particularly DNA methylation (DNAm), has offered promising insights into possible molecular pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, our study sought to investigate both the independent and joint impacts of neighborhood quality and social cohesion on three measures of DNAm aging-Horvath's epigenetic clock, Hannum's epigenetic clock, and Levine's PhenoAge-among a sample of predominately Black adults living in Detroit, MI (23)(24)(25). Given previous work suggesting biological aging biomarkers may differ by gender and with respect to area-level environmental characteristics (12,29,34), we investigated associations stratified by gender as well as in the full sample.…”
Section: Introductionmentioning
confidence: 99%
“…While apoptosis – programmed cell death – is the cause of aging, alteration of the cycle and cell immortality are the hallmarks of cancer development [4]. It is known that factors like age, sex, or stress influence telomere length [58]. However, not least important are the genetic factors, especially because several polymorphisms significantly affect telomere erosion.…”
Section: Introductionmentioning
confidence: 99%